The chambermaid [videorecording (DVD)] - Cartol, Gabriela; Quinci, Agustina; Sánchez, Teresa (Actress) (Kino Lorber, 2019)
A chambermaid at a high-end Mexico City hotel, into a beautifully observed film of rich detail. Set entirely in this alienating environment, with extended scenes taking place in the guest rooms, hallways, and cleaning facilities, this minimalist yet sumptuous movie brings to the fore Eve's hopes, dreams, and desires.